دراسة العلاقة بين تحليل البصمة الرقمية والتأثير على المستهلك خلال مراحل عملية الشراء دراسة على عينة من المواقع الإلكترونية السورية - قاسم, سامر; ديوب, جودت (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The aim of this research is to study the relationship between digital fingerprint analysis and consumer impact across the buying process. In order to achieve this, a main hypothesis has been formulated with three sub-hypotheses, according to the stages of the procurement process (pre-purchase, procurement, post-purchase). The researcher used the descriptive method, where the researcher used the questionnaire method to collect the data that were analyzed using statistical tests, the most important of which are: One- Sample T. test and Pearson Correlation. The researcher has reached several results, the most important of which are: There is a good orientation for the adoption of websites for digital fingerprint analysis as a rich source of data, in addition to a strong positive relationship between digital fingerprint analysis and influence on consumer behavior at every stage of the purchasing process. The study recommended that companies analyze the digital footprint in order to better understand customer behavior and provide information about them. هدف هذا البحث إلى دراسة العلاقة بين تحليل البصمة الرقمية والتأثير على المستهلك عبر مراحل عملية الشراء. ولتحقيق ذلك تمّ صياغة فرضية رئيسة يتفرع عنها ثلاث فرضيات فرعية، حسب مراحل عملية الشراء (مرحلة ما قبل الشراء، مرحلة الشراء، مرحلة ما بعد الشراء)، واعتمد الباحث على المنهج الوصفي، حيث استخدم الباحث أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار الارتباط الثّنائي Pearson Correlation. وقد توصل الباحث إلى عدّة نتائج أهمّها: وجود توجه جيد لاعتماد المواقع الإلكترونية لتحليلات البصمة الرقمية كمصدر غني للبيانات، بالإضافة إلى وجود علاقة موجبة قوية بين تحليل البصمة الرقمية والتأثير على سلوك المستهلك في كل مرحلة من مراحل العملية الشرائية، وأوصت الدراسة بضرورة تحليل الشركات للبصمة الرقمية من أجل فهم أكبر لسلوك العملاء، وتوفير المعلومات عنهم.